Smart Grid and wind generators: an overview of cyber threats and vulnerabilities of power supply networks - Fursov, Ihor; Yamkovyi, Klym; Shmatko, Oleksandr (Radìoelektronnì ì komp'ûternì sistemi (Online), 2022)
The subject of this study is the cyber vulnerability of wind generators, as part of the cyberphysical system of intelligent power supply networks, Smart Grid. Wind generators produce electricity for further distribution in the network between «smart» electricity consumers, which often include autonomous power systems in medical institutions, autonomous power supply of homes, charging stations for cars, etc. Wind generators operate in two aspects: in the physical and information space. Thus, a violation of the security of the information flow of a wind generator can affect the physical performance of electricity generation, and disable equipment. The study aims to identify types of cyber threats in the wind generator network based on the analysis of known attack incidents, analysis of the Smart Grid network structure, network devices, protocols, and control mechanisms of a wind generator. The tasks of the work are: review and analyze known cyberattack incidents; review the classification of cyber threats to wind farms; consider the most common methods of attacks on the cyberphysical system of wind farms; consider ways of intrusions into the information flow of the cyberphysical system wind generator; consider resilience mechanisms of wind generators in case of a cyberattack, consider the directions of further research. The methods are a systematic approach that provides a comprehensive study of the problem, quantitative and qualitative analysis of incidents of cyber attacks on wind generators, and methods of attacks. The following results were obtained: 11 large-scale known incidents of cyber attacks on the cyberphysical systems of the energy sector and smart power supply networks were analyzed, and information flow features and structure of the wind generators were considered. Main communication interfaces of the Smart Grid network were reviewed, control mechanisms for the physical parts of the wind generator system such as automatic voltage regulator, and automatic generation control were observed, vulnerable data transmission protocols, DNP3 in particular, were analyzed, possible consequences in the case of a cyber-intrusion into the network were considered. Conclusions: wind farms, as part of the Smart Grid system, are a convenient target for cyberattacks, as the number of potential ways to interfere with the information flow of the cyberphysical system is growing due to an increase in the number of sensors, communication channels in the network. This is especially important for the further development of wind farm security systems, which at the time, are not able to provide high accuracy of intrusion detection into the information flow.